Penentuan Kadar Fenolik Total, Profil Metabolit Sekunder dari Ekstrak Daun Manggis dan Pemanfaatan Potensinya dalam Sediaan Teh Herbal sebagai Antikanker - Muhammad Andry; Hanafis Sastra Winata (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background; Mangosteen leaves (Garcinia mangostana L.) have secondary metabolites, namely phenolics, flavonoids, tannins, saponins, and triterpenoids. Phenolics are one of the largest groups of compounds found in mangosteen leaves which have several pharmacological and therapeutic functions, one of which is anti-cancer. Objectives; To determine the total phenol content and profile of secondary metabolites and the type of phenolic extract of mangosteen leaves. Method; Using UV-Vis spectrophotometer Folin-Ciocalteu method with the gallic acid standard. Profile of secondary metabolites and phenolic types using LCMS. Results; Based on the research that has been done, the total phenolic content is obtained where the highest concentration is in the ethanol extract 96% (290.90 mg GAE/g extract or 29.08%), then ethyl acetate extract (161.07 mg GAE/g extract or 16, 10%). Identification of LCMS, detected 15 compounds, including 6 phenolic compounds. Phenolic compounds found were gallic acid, amarogentin, oleuropein glucoside, mandelic acid, vanillic acid, and gentisic acid.. Conclusion; Phenolic compounds can act as antioxidants by protecting body cells from damage caused by free radicals such as degenerative diseases, one of which is cancer due to free radical induction.